Identification of Human Papillomavirus genotypes in juvenile laryngeal papillomatosis. Three-year experience in a concentration hospital in Puebla, Mexico: Identificación de genotipos de Virus del Papiloma Humano en papilomatosis laríngea juvenil. Experiencia de 3 años en un hospital de concentración en Puebla, México - García-Galicia, Arturo (2023)
Background: Juvenile laryngeal papillomatosis (JLP) is a chronic benign disease from viral etiology, whose clinical course can be aggressive. In Mexico, the Human Papillomavirus (HPV) genotypes that cause this disease have been poorly studied. Objective: To identify the HPV genotypes in patients with JLP in a reference Hospital in Puebla, Mexico. Mehods: A retrospective descriptive study was performed in patients with JLP attended in a 3rd level care of the Instituto Mexicano del Seguro Social in Puebla, México, from 2018 to 2021. Medical records were revised. In all patients, HPV identification was performed by polymerase chain reaction for genomes 6, 11, 16 and 18 using specific oligonucleotides. Descriptive statistics were applied. Results: 9 patients were included, 56% women, mean age 9.5 ±5.7 years; 7 patients were HPV-11 positive and 2 HPV-6. The mean age at diagnosis was 2.35 ±1.77 years, with an average of 12 ±11.56 surgical procedures; 5 patients were tracheostomy carriers, 4 had genotype 11; 8 patients were born vaginally, but no patient had maternal genital condylomatous lesions. In the patient born by cesarean section, transmission due to sexual abuse was documented. Conclusions: The most frequent genotypes in patients with JLP in the south-central region of Mexico are HPV-6 and HPV-11, the latter one is predominating.